Empowering Through Peer Power: a Casual Learner-Mediated Collaborative Approach of Undergraduate Medical Students to Elevate Their Learning Outcomes - Umme Ammarah Omer Malik; Sana Siddiqi (Pakistan Armed Forces Medical Journal, 2024)
“Peer” a Latin word meaning “Equal” has taken  the world of education by swarm. The current era of medical education fosters a culture of learning through peers. Innovations in teaching and learning methodologies also primarily focus on peer-associated activities. Peer-assisted learning is now the most famous and productive learning strategy, which      has been innovated and customized by learners themselves.1 It involves either pairing or grouping learners based on their eagerness to learn, their ability, the skill they’ve mastered, and their age. Literature has given enough evidence about peers engaging with each other for learning in various formats: Class-wide